Comparasion of wrist arthrodesis with ulnar centralization and joint salvage with non vascularized fibular graft reconstruction surgery on distal radius giant cell tumor Campanacci 3 at single Centre - Widodo, Yohanes Aprianto Senduk; Mahyudin, Ferdiansyah; Basuki, Mohammad Hardian (Edelweiss Applied Science and Technology, 2025)
Giant cell tumor of bone (GCTB) is a benign neoplasm that is locally aggressive and mostly involves the epimetaphysis. Giant cell tumor is the sixth most common primary bone neoplasm, accounting for 20% of benign bone tumors and 5% of primary bone tumors, with the distal radius being the third most common site for GCTBs to occur, accounting for an average of 10% (8–13%) of GCTB occurrences. This study was conducted to determine the characteristics, clinical outcomes, and recurrence of GCTB of the distal radius Campanacci 3. This retrospective analytical observational study was conducted at a single center between 2015 and 2023. The study involved a comparison of wrist arthrodesis with ulnar centralization and joint salvage with non-vascularized fibular graft reconstruction in 23 patients with Campanacci 3 giant cell tumor of the distal radius. All patients were evaluated by identifying their characteristics (age, gender, tumor size, surgical procedure), functional outcomes including the Musculoskeletal Tumor Society (MSTS) score, and range of motion (ROM). The study population included slightly more females (52.2%) than males. The majority of cases occurred in the 20-30 year age range (30.4%). Most tumors were >10 cm (56.5%). Joint salvage with non-vascularized fibular graft reconstruction was performed in 56.5% of patients. There were no metastases or recurrences. A greater range of motion (>45 degrees) was observed in 52.1% of patients who underwent non-vascularized fibular graft reconstruction. 56.5% of patients achieved good MSTS scores (18-24). With the results of existing research characteristics and supported by data from other studies, there is significant evidence for joint salvage with non-vascularized fibular graft reconstruction resulting in higher functional outcomes than wrist arthrodesis.